Adaptation of the INTERGROWTH-21st neurodevelopment assessment (INTER-NDA) to the context of the English-speaking Caribbean - Randall Waechter; Roberta Evans; Sean Hanna; Toni Murray; Cassandra Mobley; Stephanie Holmes; Rashida Isaac; Rebeca Wolfe; Elbernezer Andrew; Barbara Landon; Michelle Fernandes (BMC, 2022)
Abstract Background Adaptation of standardized early child development (ECD) assessments to low- and middle-income countries can be challenging because of culture-specific factors relating to language, content, context, and tool administration, and because the reliance of these tests on specialist healthcare professionals limits their scalability in low resource settings. Methods We report the cross-cultural adaptation of an international, standardized ECD instrument, the INTERGROWTH-21st Project Neurodevelopment Assessment (INTER-NDA), measuring cognitive, language, motor and behavioural outcomes in 2-year-olds, from a UK-based English-speaking population to the English-speaking Caribbean. Children aged 22-30 months were recruited from a pre-existing randomized controlled neurodevelopment intervention study in Grenada, West Indies. Results Eight of 37 INTER-NDA items (22%) were culturally and linguistically adapted for implementation in the Caribbean context. Protocol adherence across seven newly-trained non-specialist child development assessors was 89.9%; six of the seven assessors scored ≥80%. Agreement between the expert assessor and the non-specialist child development assessors was substantial (κ = 0.89 to 1.00 (95% CI [0.58, 1.00]). The inter-rater and test-retest reliability for non-specialist child development assessors was between κ = 0.99 -1.00 (95% CI [0.98, 0.99]) and κ = 0.76 - 1.00 (95% CI [0.33, 1.00]) across all INTER-NDA domains. Conclusions The current study provides evidence to support the use of the adapted INTER-NDA by trained, non-specialist assessors to measure ECD prevalence in the English-speaking Caribbean. It also provides a methodological template for the adaptation of child developmental measures to cultural and linguistic contexts that conform to the cultural standards of the countries in which they are utilized to aid in the measurement of neurodevelopmental impairments (NDIs) in a variety of global clinical settings.